2023
DOI: 10.1002/ijc.34750
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of neutrophil extracellular traps in cancer

Jingxuan Xia,
Zhiyuan Zhang,
Yijin Huang
et al.

Abstract: Neutrophil extracellular trap (NET) is one of the defense functions of neutrophils, which has a rapid ability to kill infections and is also crucial in a variety of immune‐associated diseases including infections, tumors and autoimmune diseases. Recent studies have shown that NETs are closely related to the development of tumors. The regulatory role of NETs in tumors has been of interest to researchers. In addition to awakening latent tumor cells, NETs can also promote the proliferation and development of tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…Therefore, the reason behind the increase in NETs has attracted significant attention. Numerous studies have demonstrated that the activation of neutrophils by tumor cells and their microenvironments can lead to the release of NETs [40]. However, fewer studies have comprehensively characterized the internal changes in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the reason behind the increase in NETs has attracted significant attention. Numerous studies have demonstrated that the activation of neutrophils by tumor cells and their microenvironments can lead to the release of NETs [40]. However, fewer studies have comprehensively characterized the internal changes in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils, integral to immune defense, have been the subject of extensive research in recent years, particularly regarding the formation and function of neutrophil extracellular traps (NETs) [ 4 , 5 ]. NETs, web-like structures comprising DNA-histone complexes and proteins released by activated neutrophils, exhibit both antitumoral and pro-tumoral effects [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%